Macroeconomic Policy and Poverty Reduction - Izquierdo, Alejandro; Ames, Brian; Brown, Ward.; Devarajan, Shatayanan (Washington, D.C. : International Monetary Fund, 2001)
This pamphlet excerpts a chapter on macroeconomic policy from the Poverty Reduction Policy Source book, a guide prepared by the World Bank and IMF to assist countries in developing and strengthening their poverty reduction strategies. It probes the relationship between macroeconomic policy matters, such as growth and inflation, and the fight against poverty, and explains how sound monetary and fiscal policies-key tools of the macroeconomist-can help to spur growth and ease poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet